1963
DOI: 10.1002/app.1963.070070103
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopic reinforcement criteria for carbon black masterbatches

Abstract: IntraductionThe adequate dispersion of carbon black in rubber has long been recognized as an important factor in obtaining good physical properties in black rubber masterbatches. At the present time the most widely used methods for the microscopic evaluation of carbon black dispersions in rubber are those described by Sweitaer, Hess, and Callan' and Leigh-Dugmore.2 These methods are based on the fact that in dry mixed masterbatches the major difference between two dissimilar dispersions is likely to be in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1964
1964
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…1). Inspection of this DNA region for potential cis-acting regulatory sequences using the SIGNAL SCAN program (17) revealed the sequence motif AGGTCA (+576 to +581) which represents the half site of the consensus retinoic acid response element (RARE): PuG(G/T)TCA(N 1-5 )PuG(G/T)TCA (23). Furthermore, the sequence immediately upstream creates together with the above mentioned motif an everted repeat and a direct repeat, respectively, which we termed Hi-RARE (histocompatibility-intron RARE): 5′-TGACCC C GGGTCG G AGGTCA-3′ (+562 to +581).…”
Section: Ltk-nuclear Proteins Bind a New Retinoic Acid Response Eleme...mentioning
confidence: 99%
“…1). Inspection of this DNA region for potential cis-acting regulatory sequences using the SIGNAL SCAN program (17) revealed the sequence motif AGGTCA (+576 to +581) which represents the half site of the consensus retinoic acid response element (RARE): PuG(G/T)TCA(N 1-5 )PuG(G/T)TCA (23). Furthermore, the sequence immediately upstream creates together with the above mentioned motif an everted repeat and a direct repeat, respectively, which we termed Hi-RARE (histocompatibility-intron RARE): 5′-TGACCC C GGGTCG G AGGTCA-3′ (+562 to +581).…”
Section: Ltk-nuclear Proteins Bind a New Retinoic Acid Response Eleme...mentioning
confidence: 99%
“…These agglomerates can act as weak points in the material, and easily break down when stress is applied to the composite. 31 Therefore, the tensile strength of the unmodified silica nanoparticle reinforced PEN composites decreased with increasing silica content.…”
Section: Methodsmentioning
confidence: 99%
“…By comparing systems having good, moderate and poor carbon black dispersions, they discovered that the degree of dispersion could be correlated with field emission characteristics. Using replica techniques to study the fractured surfaces of carbon black master-batches, Prestridge (373) has shown that dispersion, grinding and bonding w'ere the most important factors for evaluating the quality of the black. By applying these criteria, the performance of a tread stock made with such master-batches can be reliably predicted.…”
Section: Polymersmentioning
confidence: 99%